2012
DOI: 10.1111/exd.12038
|View full text |Cite
|
Sign up to set email alerts
|

Improved method of differentiation, selection and amplification of human melanocytes from the hair follicle cell pool

Abstract: Hair root harbours a complex cell pool with an immense developmental potential. Several lineages, including skin, can be differentiated from the multipotent to pluripotent cells of outer root sheath (ORS) of hair follicle. Outer root sheath presents the most opulent non-invasively gained adult stem cell source known. For the purposes of cultivating melanocytes designated for graft-based treatments of depigmentation disorders, we have established an ex vivo/in vitro cultivation method by introducing several met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
59
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(60 citation statements)
references
References 31 publications
1
59
0
Order By: Relevance
“…1) were synthesized and characterized as reported previously. 13 C NMR spectra were recorded in D 2 O with a 400 MHz device (Bruker Corporation, 5 mm BBFO smart probe) in order to analyze the substituent distribution of sHA derivatives. The following sulfation reaction of TBA-HA was performed under argon in DMF at room temperature.…”
Section: Preparation and Analytics Of Gag Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…1) were synthesized and characterized as reported previously. 13 C NMR spectra were recorded in D 2 O with a 400 MHz device (Bruker Corporation, 5 mm BBFO smart probe) in order to analyze the substituent distribution of sHA derivatives. The following sulfation reaction of TBA-HA was performed under argon in DMF at room temperature.…”
Section: Preparation and Analytics Of Gag Derivativesmentioning
confidence: 99%
“…13 C NMR spectra of hyaluronic acid and of the sulfated derivatives sHA1 and sHA4. quantification was calculated by the means of the ΔΔC T method 64 following calibration to the value of PS cultures and set at 1.0.…”
mentioning
confidence: 99%
“…As ORS cells include pluripotent neural crest stem cell (NCSC)-like stem cells and quiescent stem cells that have potential to be differentiated into various cell types, ORS cells are a valuable resource in regenerative medicine [106] . Dieckmann et al demonstrated methods to isolate melanocytes from ORS cells in human anagen hair and propagated them in vivo; moreover, the yields of the melanocytes could be improved by a sequential method [107,108] . Although this method is not yet used in the clinical setting, the source of the melanocytes could be the MelSCs in ORS and this represents a promising method for biologic therapeutics in the near future.…”
Section: Expert Opinion: Potential Clinical Applications Of Melanomentioning
confidence: 99%
“…Most of the ORS subpopulations are promising candidates for regenerative therapies. The ORS cell pool is easily accessible by harmless plucking of hair and therefore valuable for approaches that require non‐invasive sampling, whether for research or therapeutic purposes …”
Section: Introductionmentioning
confidence: 99%